LDHA-mediated ROS generation in chondrocytes is a potential therapeutic target for osteoarthritis - Manoj Arra (Nature Portfolio, 2020)
Chondrocytes have altered cellular metabolism in the context of osteoarthritis, but whether and how these changes are associated with inflammation is a controversial area. Here the authors show that inflammatory NF-κB signalling drives a glycolytic shift in chondrocytes and the production of ROS, which drives cartilage catabolism.